2006
DOI: 10.1016/j.jsgi.2005.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding the Molecular Causes of Diabetes-Induced Birth Defects

Abstract: Excess glucose metabolism by embryos resulting from maternal hyperglycemia disturbs a complex network of biochemical pathways, leading to oxidative stress. Oxidative stress inhibits expression of genes, such as Pax3, which control essential developmental processes. Pax3 protein is required during neural tube development to suppress p53-dependent cell death and consequent abortion of neural tube closure, but is not required to control expression of genes that direct neural tube closure. Impaired embryo gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 80 publications
3
77
1
Order By: Relevance
“…Moreover, hyperglycaemia induces apoptosis in early organogenesis in pre-and post-implantation rodent embryos through cell-death effector pathways [25][26][27][28][29]. Also, neural tube defects (NTDs) are associated with apoptosis in the offspring of diabetic mice [30,31]. Taken together, these findings support the assumption that diabetes-induced inappropriate apoptosis in embryos might lead to NTDs.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, hyperglycaemia induces apoptosis in early organogenesis in pre-and post-implantation rodent embryos through cell-death effector pathways [25][26][27][28][29]. Also, neural tube defects (NTDs) are associated with apoptosis in the offspring of diabetic mice [30,31]. Taken together, these findings support the assumption that diabetes-induced inappropriate apoptosis in embryos might lead to NTDs.…”
Section: Introductionmentioning
confidence: 52%
“…In addition, diabetes-induced inappropriate apoptosis in embryos during neurulation has been demonstrated to be one of the mechanisms leading to neural tube defects [31]. We therefore assayed apoptosis in the embryos of DM and non-DM, WT or TRX-Tg mice during organogenesis, by histochemical analysis of apoptotic cells and cleaved caspase-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal mice, blood glucose increases at gd4.5 (32). All pregnant NOD mice (normoglycemic, n ϭ 5; pre-diabetic, n ϭ 7; diabetic, n ϭ 7) displayed significant increases in blood glucose from their individual baselines (three prior measurements; Fig.…”
Section: Pregnancy Accelerates Progression To Overt Diabetesmentioning
confidence: 90%
“…It has been widely shown that maternal diabetes induces hypoxia, oxidative stress and other metabolic disturbances in the embryo [31] and these changes alter several signalling pathways and molecules which have been proposed to be the major causative factors for the diabetes-induced malformations leading to embryopathy. For example, the oxidative stress caused by hyperglycemia has been shown to disrupt the expression of genes such as Pax3 that is involved in neural tube formation which explains in part that hyperglycemia-induced oxidative stress alters gene expression leading to NTD [32] . Hyperglycemia-induced birth defects are attributed to the excessive production of reactive oxygen species (ROS) which has been shown to cause oxidative stress and subsequently increase the risk for fetal malformations [33,34] .…”
Section: Characterisation Of Metabolic Pathways In Ntdsmentioning
confidence: 99%